Foliar application of commercially available micro and macronutrients for the management of flower thrips and pod borers of mung bean - Md. Altaf Hossain,; Md. Ahsanul Haque,; Md. Mahbubur Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The production of mung bean is facing a serious threat from insect pests, notably the flower thrips (Megalurothrips distalis) and pod borers (Maruca vitrata, Helicoverpa armigera, Spodoptera litura, Eucrysops sp.). In response, growers often resort to chemical pesticides, despite their adverse environmental and health impacts. However, an alternative approach involves substituting chemical pesticides with foliar applications of micro and macronutrients, proven effective in controlling insect pests in various crops. This study investigated the efficacy of such nutrients against flower thrips and pod borer infestations in mung bean. Conducted over two consecutive years (2020 and 2021) at the Pulses Research Centre, Bangladesh Agricultural Research Institute (BARI), Ishurdi, Pabna, and Regional Agricultural Research Station, BARI, Rahmatpur, Barishal, Bangladesh, the research reveals those foliar nutrient applications notably reduced flower thrips infestation in 2020, albeit to a lesser extent in 2021. The most substantial reduction in flower infestation occurred in plots treated with Thiovit (80% Sulphur) and Nutra-phos (24% Phosphorus+20% Calcium+6% Sulphur+12% Zinc) at the range of 13.5-24.5 and 13.5-18.6%. Nutrient applications also significantly decreased pod borer infestation, with the greatest reduction (36.0-40.0%) observed in plots sprayed with Muriate of Potash (60% Potassium) in both years, followed by Nutra-phos, Thiovit and McChili+Solubor (Zn:10%+B:20%). Although yield increased non-significantly compared to the control in both years and locations, the highest yield was observed in Nutra-phos sprayed plots (1112.0-1865.0 kg/ha), followed by Thiovit. However, the greatest benefit was derived from Thiovit, followed by Nutra-phos and McChili+Solubor treated plots. In conclusion, Thiovit, Nutra-phos or McChili+Solubor are recommended for foliar application in mung bean cultivation to effectively control flower thrips and pod borer infestations, offering both efficacy and cost-efficiency as alternatives to chemical pesticides.